Arenobufagin activates p53 to trigger esophageal squamous cell carcinoma cell apoptosis in vitro and in vivo - Lv, Junhong (Onco Targets Ther, 2017)
Esophageal squamous cell carcinoma (ESCC) is often diagnosed at late incurable stage and lacks effective treatment strategy. Bufadienolides are cardiotonic steroids isolated from the skin and parotid venom glands of the toad Bufo bufo gargarizans Cantor with novel anticancer activity. However, there is little information about the effects and action mechanisms of bufadienolides on ESCC cells. In this study, the in vitro and in vivo anti-ESCC activities of bufadienolides, including bufalin (Bu) and arenobufagin (ArBu), were examined and the underlying molecular mechanisms were elucidated. The results showed that ArBu exhibited higher anticancer efficacy than Bu against a panel of five ESCC cells, with IC(50) values ranging from 0.8 μM to 3.6 μM. However, ArBu showed lower toxicity toward Het-1A human normal esophageal squamous cells, indicating its great selectivity between cancer and normal cells. Moreover, ArBu effectively induced ESCC cell apoptosis mainly by triggering caspase activation through intrinsic and extrinsic pathways. Treatment of ESCC cells also significantly activated p53 signaling by enhancing its phosphorylation. Interestingly, transfection of cells with p53 small interfering RNA significantly inhibited the ArBu-induced p53 phosphorylation and the overall apoptotic cell death. Furthermore, ArBu also demonstrated novel in vivo anticancer efficacy by inhibiting the tumor growth through activation of p53 pathway. Taken together, these results demonstrate the p53-targeting therapeutic potential of bufadienolides against ESCC.